METHODICAL APPROACHES TO DIAGNOSIS OF FINANCIAL SECURITY OF ENTERPRISE TAKING INTO ACCOUNT THE FACTOR OF COMPETITIVENESS - Krynytsia, Sergii; Tryhub, Julia (Socio-economic relations in the digital society, 2020)
The purpose of the article is to improve the methodology of diagnostics of financial security of the enterprise taking into account the factor of its competitiveness. The relationship and interaction between the financial security of the enterprise and its competitiveness. The problematic issues of the influence of the enterprise’s competitiveness on its financial security and methods of diagnostics of the financial security of the enterprise are investigated. The factors in the relationship between financial security and competitiveness of the enterprise have been structured. It is proved that both phenomena are caused by the influence of the external environment, which in a market economy is constantly changing. But, at the same time, they depend on internal factors, which include the availability and sufficiency of the financial potential of the enterprise and the quality of the management system. A critical analysis of methodological approaches to assessing the financial security of the enterprise and proposed to calculate the integrated indicator of financial security of the enterprise based on a qualitative assessment of the level of indicator values, namely the mechanism of conversion of quantitative multidimensional indicator values based on Harrington’s desirability function. For each indicator, a five-interval evaluation scale is obtained, which allows not only to obtain a qualitative definition of the actual value, but also serves as an indicator of the impact of competitiveness on the financial security of the enterprise.